PTEN deletion potentiates invasion of colorectal cancer spheroidal cells through 3D Matrigel. Issue 3 (27th January 2015) - Chandrasekaran, Siddarth; Deng, Huanyun; Fang, Ye
Abstract : The label-free single cell 3D 2 invasion assay enables real-time quantification of the invasion of spheroidal cells through 3D Matrigel and provides insights into the role of PTEN in colorectal cancer cell invasion. Abstract : PTEN (phosphatase and tensin homolog), a tumour suppressor negatively regulating the PI3K signalling pathway, is the second most frequently mutated gene in human cancers. Decreased PTEN expression is correlated with colorectal cancer metastases and poor patient survival. Three dimensional (3D) multicellular spheroid models have been postulated to bridge the gap between 2D cell models and animal models for cancer research and drug discovery. However, little is known about the impact of PTEN deletion on the invasion of colon cancer spheroidal cells through a 3D extracellular matrix, and current techniques are limited in their ability to study in vitro 3D cell models in real-time. Here, we investigated the migration and invasion behaviours of the colon cancer cell line HCT116 and its PTEN−/− isogenic cell line using three different in vitro assays, wound healing, transwell invasion, and label-free single cell 3D 2 invasion assays enabled by a resonant waveguide grating (RWG) biosensor. Light microscopic and RWG imaging showed that PTEN deletion influences the spheroid formation of HCT116 cells at high seeding density, and accelerates the spontaneous transfer from the spheroid to substrate surfaces. In vitro migration and invasion assays showed that PTEN knockout increases the 2D migration speed of HCT116 cells, and the invasion rate of individual cells through Matrigel or cells in the spheroid through 3D Matrigel; moreover, the PI3K inhibitor treatment drastically reduces the invasiveness of both cell lines. This study suggests that PTEN knockout potentiates the invasiveness of colorectal cancer spheroidal cells through a 3D extracellular matrix, and the label-free single cell assay is a powerful tool for investigating cancer cell invasion, in particular using 3D cell models.